Self-medication for prevention of COVID-19 in university students of the northeast of Mexico - González González, María del Rosario; Yeverino Gutiérrez, Myrna Laura; Ramírez Estrada, Karla; González Santiago, Omar (Asociación INTERCIENCIA, 2022)
The COVID-19 pandemic has provoked an enormous impact around the world. The objective of this study was to determine the prevalence of self-medication for the prevention of COVID-19 during 2020 in a sample of university students from the northeast of Mexico. An electronic survey composed of two sections was used; the first section collects sociodemographic information, and the second section information related to self-medication for prevention of COVID-19. A totalof 284 students responded to the survey, 26% reports having self-medicated to prevent COVID-19, and 34.5% reports having a family member that self-medicated to prevent COVID-19 infection. The main products used to prevent infection were vitamins, NSAIDs, and herbal products. It is concluded that, in 2021, a significant percentage of university students in northeastern Mexico reported self-medication to prevent COVID-19 infection.